Orthokeratology for myopia control: a three-year longitudinal study on axial length modulation influenced by baseline age and spherical equivalent - Xiaoxue Hu; Zixun Wang; Boxuan Sun; Xiang Wan; Feng Chang; Weiping Lin; Ruihua Wei (BMC Ophthalmology)
Abstract Background Myopia, particularly high myopia (spherical equivalent (SE) ≤ -6.00D), poses significant risks of irreversible vision loss due to ocular complications. Orthokeratology (Ortho-k), a corneal reshaping intervention, has demonstrated efficacy in slowing axial length (AL) elongation. However, the influence of baseline age and SE on long-term AL modulation remains inadequately explored, with limited evidence on AL shortening during treatment. Objective This study aimed to evaluate the impact of baseline age and SE on AL control efficacy during ortho-k treatment, assess the long-term effects of AL shortening, and identify potential mechanisms underlying these observations. Methods A retrospective cohort study analyzed 1,303 children (7–16 years old) undergoing ortho-k treatment during 2020–2025. Participants were stratified into four groups by baseline age (11 years) and SE (-3.00D): LH (low age/high SE), LL (low age/low SE), HL (high age/low SE), and HH (high age/high SE). AL measurements were calibrated for physiological growth, with regression defined as ≥ 0.05 mm shortening. Statistical analysis compared AL progression and regression rates across groups over a three-year period. Results The HH group exhibited superior AL control, with rates of 85.95% excellent response in the first year, significantly lower than all other groups (p < 0.01). AL shortening occurred most prominently in HH (23.90% for 2 years; mean: −0.16 ± 0.10 mm) and persisted through Year 3. In contrast, the LL group showed minimal AL regression (1.89% for 3 years; mean: −0.17 ± 0.09 mm) with rates of 13.21% excellent response. The HL and LH groups, both in AL control excellence rate and in AL regression performance, were intermediate between the HH and LL groups. Conclusion Ortho-k effectiveness in AL control is critically dependent on baseline age and SE. Children with older age (≥ 11 years) and higher baseline myopia (SE ≤ -3.00D) experienced optimal AL suppression and regression, likely due to enhanced corneal remodeling and defocus effects. Younger children (≤ 11 years) with lower SE may require adjunct therapies for significant AL control.